(untitled) (International Journal of Food and Nutritional Sciences, 2023)
In Sanskrit literature surya means sun, and the word namaskar means salutation. The present study was to investigate the suryanamaskar practices and it impact on anaerobic capacity and fatigue index among handball players. For this investigation, the handball players were picked by Regional College of Physical Education, North Tiripura, India using a simple random method. Twenty handball players were randomly allocated to a suryanamaskar practices group and a control group for this study (10 each). For six weeks, the suryanamaskar group did suryanamaskar practices with two dimensions which mean fast and slow suryanamaskar practices for 45-60 minutes each day in the presence of trained yogic trainer and researcher. The control group did not go through any type of specific training. The pre and post controlled randomized design was used for this study. The following selected variables were tested by standardized tools. The pre and post data were collected before and immediately after the training period. The selected variables were anaerobic capacity and fatigue index was tested by standardized tests RAST test method. The collected data were analyzed by using standardized statistical technique. The data was entered into excel spreadsheet, tabulated and subjected to statistical analysis. Various statistical measures are such as Mean, dependent-‘t’ test and analysis of covariance (ANCOVA). The results were concluded to be statistically considered significant with 0.05 level. The result of the study reveals that suryanamaskar practices had brought out significant positive changes on anaerobic capacity and fatigue index. Regular suryanamaskar practices increases the amount of oxygen delivered to the tissues and removal of carbon dioxide from the body.